Autocratic legitimation in Iran: Ali Khamenei's discourse on regime "insiders" and "outsiders". Issue 7 (3rd October 2018) - Selvik, Kjetil
ABSTRACT: The article analyses Ali Khamenei's discourse on insiders and outsiders in the Islamic Republic of Iran, arguing that it shows the leader of an electoral revolutionary regime striving to counter elite fragmentation and growing democratic demands. It studies identity demarcation as a tool of autocratic legitimation. In a political system where the possibility to access political positions depends on supporting a belief-system, all cadres share a basic identity, which rulers can exploit to draw boundaries between "us" and "them". The analysis reveals how Iran's leader capitalizes on the existence of an insider-outsider divide to promote ideas about an imagined "we" of the regime. The "we" is portrayed as an Islamic we, fully committed to his rule. The article maintains that Khamenei developed this discourse in response to the challenge of the Iranian reform movement. It analyses, first, the context in which the discourse emerged and, second, the discursive strategy itself, to substantiate the claim. It concludes that the discourse had two essential aims in the containment (1997–2003) and crushing (2009–2010) of the pro-democracy reformist and Green movements: to de-legitimate Khamenei's opponents through othering and to legitimate the counter-mobilization of repressive agents.